Corporate integration, competitiveness and financial performance: suppliers’ perspective - Parlak, Deniz. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
The purpose of this study is to examine the nature and the consequences of the relationship between suppliers and their industrial buyers and to search for the effect of different types of relationships on supplier’s financial performance. Though conventional arm’s length relations and integrated ties are viewed as the two ends of the spectrum, each has its own benefits and costs. In this study, it is hypothesized that in contrast to arm’s length relationships, integrated relations have some unique characteristics that make them more innovative and more competitive, but given the costs and benefits of each type of relationship, to maximize the financial performance, the most efficient strategy for suppliers is to follow not a single but a portfolio of customer relationships characterized by different degrees of involvement. The hypotheses are tested on a sample of 106 firms supplying to automotive, electronics, white goods and construction industries. The findings support a two way relationship among four out of the five integration intensity factors, namely cooperation, trust, communication and joint conflict resolution, and three out of the four relational outcome variables which are product quality, process flexibility and cost leadership. Innovativeness is found to be an important mediating variable. Financial ratio analysis shows that despite the positive association between integration intensity and relational outcome measures, the financial return is maximized when suppliers follow not a single relationship but a portfolio of relationships strategy.
Keywords: Industrial procurement.